Parentification as a Process of Role Reversal in the Family - Żłobicki, Wiktor (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2022)
The study presents the issue of parentification, i.e. the child undertaking tasks belonging to adults. As a result of role reversal in the family, a child sacrifices their own needs for the sake of the instrumental and/or emotional needs of the parent. Parentified children have to cope not only with duties exceeding their normal abilities, but also in adult life they experience the effects of the role reversal in the family. More often than not, parentificationis transgenerational and the mechanism of its emergence involves a tleast three successive generations, with a particular focus on role reversal with one’s own parents. The aim of this study is to disseminate knowledge about the causes, conditions and prevention of parentification. Parentification of children in the family results from an intergenerational message and promotes the development of personality disorders.
Keywords: parentification; child; family; parental role; psychotherapy